EVALUATION OF THE EFFECTIVENESS OF MOBILE INSTRUMENT PREPERATION BOXES IN CARDIOVASCULAR INTERVENTIONS AT VINMEC TIMES CITY INTERNATIONAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the results of the work using a portable box for the preparation of printed instruments outside the printed box.Method: Retrospective study comparing the conventional group with the group using a standard portable box. The analysis was performed in three time periods: phase 1 (I quarter of 2022 and I quarter of 2023) with 45 cases of need; phase 2 (IV quarter of 2022 and IV quarter of 2023) with 75 cases; phase 3 (I quarter of 2023 and I quarter of 2024) with 20 cases randomly selected from 60 cases (k = 3). The time can be recorded by a timer, counting from the start of the pulse to the end of the procedure, in seconds, then converted to the hour:minute:second format.Results: The average intervention time by year is as follows: 2022 is 01:49:34/case, 2023 is 01:28:53/case. The average time of IV quarter of 2022 is 01:32:59/case, IV quarter of 2023 is 01:22:18/case, I quarter of 2023 is 01:53:38/case, and I quarter of 2024 is 01:35:11/case. A total of 140 cases were compared between the two groups. Using the mobile box reduced the average time by 20 minutes and 0.6 seconds/case, equivalent to a total of 2800 minutes or 46.7 hours, equivalent to nearly 6 working days.Conclusion: Using the mobile box helps to optimize the time for instrument preparation and significantly shorten the time for vascular intervention, bringing about clear practical effects.
Keywords: Mobile instrument preparation box, cardiovascular printing, results.